Variables associated with successful implementation of performance management system-a study on Robi Axiata Limited - Nadia, Ilmi Tabassum (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.